Optimalisasi Bonus Demografi Dan Peningkatan Kualitas Sumber Daya Manusia Dalam Perspektif Ekonomi Islam Ibn Khaldun : Studi Kasus Kabupaten Belitung Timur - Maliki, Abd.; Arif, Zainal (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2024)
This research discusses the optimisation of the demographic bonus and the improvement of the quality of human resources in East Belitung Regency from the perspective of Ibn Khaldun's Islamic economics. The demographic analysis shows a decade-long demographic bonus, but the economy has not shown optimal growth. The quality of human resources is low as reflected in education, health and informal employment. The research methodology uses a qualitative approach with data analysis from the 2020 Census, the March 2020 National Socio-Economic Survey and local economic data. Key findings include the state of the demographic dividend, which has not reached its potential, the need to improve the quality of education and health, and the dominance of the unsustainable mining sector. From the perspective of Ibn Khaldun's Islamic economics, this research emphasises the importance of education as a foundation for development, the role of government in policies that support a sustainable economy, and efforts to improve skills. The main conclusion offers recommendations for local government, measures to improve the quality of human resources, and the implementation of Ibn Khaldun's concept in supporting sustainable economic development.